1999
DOI: 10.1007/s100530050492
|View full text |Cite
|
Sign up to set email alerts
|

Two photon photoemission of deposited silver clusters

Abstract: We use time resolved two photon photoemission to study the stability of size selected silver clusters deposited onto highly oriented pyrolytic graphite (HOPG) substrates. Size-selected Ag + n clusters (n = 2 − 9) are deposited at low coverage onto HOPG surfaces at liquid nitrogen temperatures. After deposition, the samples are irradiated by a series of ultrashort laser pulse pairs. Photoelectrons created by two photon photoemission are collected in a magnetic bottle type time-of-flight photoelectron spectromet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…A steep increase of the photoelectron yield is visible at 155 K. This increase shows, that the plasmon resonance of the grown nanoparticles begins to shift into the photon energy. The excitation path changes compared to the low temperature regime [6], where the first photon is absorbed by the substrate. With the formation of silver nanoparticles the predominant part of the signal results from absorption of both photons inside the adsorbate.…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…A steep increase of the photoelectron yield is visible at 155 K. This increase shows, that the plasmon resonance of the grown nanoparticles begins to shift into the photon energy. The excitation path changes compared to the low temperature regime [6], where the first photon is absorbed by the substrate. With the formation of silver nanoparticles the predominant part of the signal results from absorption of both photons inside the adsorbate.…”
Section: Methodsmentioning
confidence: 98%
“…To our knowledge no experiments, which investigate the temperature dependent coalescence of the silver clusters, exist so far. In earlier 2PPE-experiments [6] we observed the cluster size dependence of the 2PPE-spectra at a sample temperature of 100 K. The work function of the sample showed a pronounced odd/even effect, which is caused by the different charge transfer of odd-and even-numbered silver clusters to the substrate. From these observations we concluded that the clusters do not coalesce but retain their identity on the substrate at 100 K. The surface of the HOPG substrate is characterized by large flat terraces, which are separated by nearly parallel steps [8].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation